The Urgency of Fiqh Education and Family Role in The Middle of Covid-19 Pandemic For Students In School and Madrasah - Firman Mansir (Kamaya: Jurnal Ilmu Agama, 2021)
This Research explains that fiqh education and family roles in the middle covid-19 pandemy, fiqh comes from Arabic that has the sense of understanding or knowledge of thing. While based on the term, fiqh is an understanding of Islamic laws that are in accordance with the Qur'an and Hadith. Education in Islam is often referred to as al-tarbiyah that comes from the root word rabb that has the basic meaning of growing, developing, maintaining, regulating, and preserving. Based on health experts, Covid-19 is a disease caused by the acute respiratory syndrome coronavirus 2 when it attacks humans. This virus is very dangerous. Therefore, the government has implemented several policies to reduce the potential for covid-19 transmission, any activities that involve direct interaction are limited, this has an impact, especially on the education system, that will have high potential for the transmission of the Covid-19 virus. The government took a policy to close schools, madrasas, universities and Islamic boarding schools. Thus, learning activities could not take place as usual. It is conducted out by distance, or online learning.